Synchronization of maritime economic policy and marine tourism development: A critical review of the blue growth concept in East Java - Jery Christianto; Leonardo Gunawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study aims to analyse the synchronization between Maritime Economic Policy (MEP) and Marine Tourism Destination Development (MTDD) within the blue growth framework in East Java, Indonesia, emphasizing the integration of governance, digital innovation, and stakeholder collaboration for sustainable maritime development. A qualitative integrative literature review method, using data sourced from Reputable Journals. Thematic analysis used to identify patterns of convergence, synergy, and gaps between MEP and MTDD. The findings reveal that East Java has implemented innovative governance practices, including the CETTAR digital platform and community based institutions such as BUMDes, which enhance transparency, coordination, and stakeholder engagement. However, key challenges remain, including fragmented institutional coordination, limited local participation, and inadequate policy integration across government levels. To address these, the study proposes a multidimensional MTDD framework encompassing environmental, economic, social, governance, and innovation components aligned with MEP’s strategic pillars. The results emphasize the importance of adaptive governance, transparency, and inclusive participation to balance economic growth with marine ecosystem preservation. This research contributes to both theory and practice by providing a holistic multidimensional model for harmonizing maritime economic and tourism development policies, offering strategic insights and actionable guidance for policymakers, stakeholders, and researchers seeking to advance sustainable coastal and maritime development in East Java and similar regions. The model harmonizes maritime economic policy with tourism development by integrating environmental, economic, social, governance, and innovation pillars.